Application of minimally invasive approaches to pelvic exenteration for locally advanced and locally recurrent pelvic malignancy - A narrative review of outcomes in an evolving field. Issue 11 (November 2022) - Casey, Laura; Larach, José Tomás; Waters, Peadar S.; Kong, Joseph CH.; McCormick, Jacob J.; Heriot, Alexander G.; Warrier, Satish K.
Abstract: Introduction: Minimally invasive surgical techniques are being successfully used to treat locally advanced and recurrent pelvic malignancy of colorectal origin. This review aims to describe the application of minimally invasive approaches to pelvic exenteration and compare current reported surgical outcomes. Methods and results: A literature search was performed of PubMed, Google Scholar and EMBASE for studies on pelvic exenteration with locally advanced or recurrent rectal cancer utilising minimally invasive techniques. A total of 22 studies were reviewed, including four case reports describing novel approaches. Discussion: Laparoscopic, robotic and trans -anal total mesenteric excision (TaTME) aided pelvic exenteration methods have recently demonstrated low post-operative morbidity and mortality trends. Minimally invasive methods also have improved rates of R0 resection in modest cohort studies. Hybrid methods have also been proposed to overcome observed technical difficulties such as the narrow male pelvis and obese habitus. There is still limited data beyond case report and small cohort studies on challenging patient groups such as those with recurrent rectal cancer or bony involvement, as a consequence of patient selection for these novel approaches. Conclusion: International, multicentre studies have provided the best opportunity to explore efficacy of these methods on a larger scale. Further research is required into patient selection, safety and long-term outcomes of these approaches within high volume centres practicing beyond the surgical learning curve. Highlights: Minimally invasive surgical techniques are being successfully applied to pelvic exenteration for locally advanced and recurrent rectal cancer Hybrid minimally invasive methods have been proposed to overcome observed technical difficulties Although minimally invasive approaches incur a longer operative time, significantly reduced blood loss, 30 day morbidity and mortality has been reported. Collaborative trials from high volume centres may provide sufficient data for statistically significant trends in surgical outcomes Further research into the patient selection, efficacy, safety and long-term outcomes of these approaches is needed